Prevalence of generalized joint hypermobility, arthralgia and motor competence in 10-year-old school children. - Remvig, Lars; Kümmel, Cristina; Kristensen, Jens Halkjær; Boas, Gudrun; Juul-Kristensen, Birgit (International Musculoskeletal Medicine, 2011)
Objectives Diverging results exist for children regarding the relation between generalized joint hypermobility (GJH) and musculoskeletal complaints, as well as relations between GJH and insufficient motor development, and/or reduced physical activity level. The main purposes were to (1) survey the prevalence of GJH and of benign joint hypermobility syndrome (BJHS) in 10-year-old children, (2) compare children with and without GJH and BJHS regarding motor competence, physical activity, and musculoskeletal pain and injuries. Subjects and methods All fourth-grade children in a Copenhagen municipality were invited to be clinically examined and tested for motor competence, and to answer a questionnaire about musculoskeletal pain, injuries, and physical activity. Results The final cohort comprised 315 Caucasian children, 50.5% girls and 54% boys. GJH prevalence was 35.6, 16.8, or 11.1%, depending on GJH cut level 4, 5, or 6, without significant motor competence difference between non-GJH and GJH children. Girls with GJH6 compared to non-GJH6 had insignificantly higher vertical jump height, and boys with GJH6 significantly shorter hand reaction time. In total, 108 Caucasian children answered the questionnaire, 56.5% girls and 43.5% boys. Nineteen fulfilled the criterion for BJHS, without difference in frequency of musculoskeletal pain and injuries, motor competence tests or physical activity compared with non-BJHS. Conclusion GJH prevalence in this cohort is comparable to previous results. Increased pain or frequency of injures were not related to GJH. Children with GJH6 performed better in motor competence tests. Longitudinal studies are recommended to detect influences of GJH on the musculoskeletal system over time.